Considerable cracking in the foundation slab in a multi-storey underground garage - Maj Marek; Tamrazyan Ashot; Ubysz Andrzej (MATEC Web of Conferences, 2019)
Multilevel underground garages are often an ambitious geotechnical task in urban agglomeration. Lower levels of foundation slabs are often located below the groundwater level, which requires effective protection of the structure against groundwater invasion. The constructor’s task is to design slabs and walls so that no cracks will form to allow groundwater infiltration. In practice, this requires the development of a correct recipe for concrete; moreover, all factors affecting the total state of normal and tangential stresses as well as technologies allowing for correct execution of the facility must be considered. Additionally, long-term destructive factors ought to be taken into account. The article presents problems that arose during the use of an underground garage, which occurred as a result of failure to take into account at the design stage some rheological processes, as well as the assessment of the possibility of using the facility despite the damage.